Age Influences Microglial Activation After Cuprizone-Induced Demyelination - Klein, Barbara; Mrowetz, Heike; Barker, Conor Michael; Lange, Simona; Rivera, Francisco J.; Aigner, Ludwig (Frontiers in Aging Neuroscience, 2018)
Multiple sclerosis (MS) is a chronic inflammatory CNS disease, which causes demyelinated lesions and damages white and gray matter regions. Aging is a significant factor in the progression of MS, and microglia, the immune cells of the CNS tissue, play an important role in all disease stages. During aging, microglia are functionally altered. These age-related changes probably already begin early and might influence the progression of CNS pathologies. The aim of the present study was to investigate whether microglia in the middle-aged CNS already react differently to demyelination. For this purpose, several microglia markers (ionized calcium binding adaptor molecule 1 (Iba-1), P2RY12, F4/80, CD68, major histocompatibility complex II (MHCII), macrophage receptor with collagenous structure (Marco), Translocator protein 18 kD (TSPO), CD206, and CD163) were analyzed in the acute cuprizone demyelination model in young (2-month-old) and middle-aged (10-month-old) mice. In addition, microglial proliferation was quantified using double-labeling with proliferating cell nuclear antigen (PCNA) and bromodeoxyuridine (BrdU), which was injected with the onset of remyelination. To compare age-related microglial changes during de- and remyelination in both gray and white matter, the hilus of the dorsal hippocampal dentate gyrus (DG) and the splenium of the corpus callosum (CC) were analyzed in parallel. Age-related changes in microglia of healthy controls were more pronounced in the analyzed gray matter region (higher levels of F4/80 and Marco as well as lower expression of CD68 in middle-aged mice). During de- and remyelination, a stronger increase of the microglial markers Iba-1, CD68 and TSPO was observed in the splenium of the younger groups. There was a significant reduction of P2RY12 during demyelination, however, this was age- and region-dependent. The induction of the anti-inflammatory markers CD206 and CD163 was stronger in the middle-aged group, but also differed between the two analyzed regions. De- and remyelination led to a significant increase in PCNA+ microglia only in young groups within the white matter region. The number of BrdU+ microglia was not changed during de- or remyelination. These results clearly show that microglia are already altered during middle-age and also react differently to CNS demyelination, however, this is highly region-dependent.